Carnosol protects against spinal cord injury through Nrf-2 upregulation. (2nd January 2016) - Wang, Zhi-Hui; Xie, Yu-Xi; Zhang, Jun-Wei; Qiu, Xiao-Hua; Cheng, Ai-Bin; Tian, Li; Ma, Bao-Yin; Hou, Yu-Bo
Abstract: Background : Carnosol is an ortho-diphenolic diterpene with excellent antioxidant potential. The present study was designed to identify the protective role of carnosol against spinal cord injury (SCI)-induced oxidative stress and inflammation in Wistar rats. Methods : In the present study, oxidative stress status was determined through estimating total antioxidant capacity, total oxidant status, lipid peroxide content, protein carbonyl and sulfhydryl levels, reactive oxygen species (ROS), antioxidant status (superoxide-dismutase, catalase, glutathione, glutathione peroxidase, glutathione- S -transferase). Inflammatory effects were determined by analyzing the expression of NF-κB and COX-2 through Western blot analysis. Further, carnosol-mediated redox homeostasis was analyzed by determining p-AKT and Nrf-2 levels. Results : SCI resulted in a significant increase in oxidative stress status through increased ROS generation, total oxidant levels, lipid peroxide content, protein carbonyl and sulfhydryl levels. The antioxidant status in SCI rats was significantly reduced, indicating imbalance in redox status. In addition, the expression of NF-κB and COX-2 was significantly upregulated, while p-AKT and Nrf-2 levels were downregulated in SCI rats. However, treatment with carnosol showed a significant enhancement in the antioxidant status with concomitant decline in oxidative stress parameters. Further, carnosol treatment regulated the key proteins in inflammation and redox status through significant downregulation of NF-κB and COX-2 levels and upregulation of p-AKT and Nrf-2 expression. Conclusion : Thus, the present study shows for the first time on the protective role of carnosol against SCI-induced oxidative stress and inflammation through modulating NF-κB, COX-2 and Nrf-2 levels in Wistar rats.